2016
DOI: 10.1080/00913847.2016.1200443
|View full text |Cite|
|
Sign up to set email alerts
|

Impairment based rehabilitation for patellofemoral pain patients

Abstract: Patellofemoral pain is a common knee pathology that affects a wide range of active individuals. These individuals often seek medical care, with 25% of all patients seen in sports medicine clinics being treated for patellofemoral pain. While conservative treatment produce beneficial short-term results, individuals with patellofemoral pain often have long-term pain and decreased quality of life for many years following their diagnosis. One of the challenges for treating this chronic condition is the heterogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 87 publications
0
18
0
1
Order By: Relevance
“…27,34 Individuals completed a 4-week rehabilitation program in a laboratory setting (3 supervised visits a week) that incorporated quadriceps; gluteals; and core strengthening, stretching, and balance training, using an impairment-based paradigm (Table 3). 35 This rehabilitation program is a modified version of a program that produced improvements in strength and subjective function in individuals with PFP 30 and was individualized to each patient based on evaluation findings in each case. A single certified athletic trainer (A.N.M.)…”
Section: Interventionsmentioning
confidence: 99%
“…27,34 Individuals completed a 4-week rehabilitation program in a laboratory setting (3 supervised visits a week) that incorporated quadriceps; gluteals; and core strengthening, stretching, and balance training, using an impairment-based paradigm (Table 3). 35 This rehabilitation program is a modified version of a program that produced improvements in strength and subjective function in individuals with PFP 30 and was individualized to each patient based on evaluation findings in each case. A single certified athletic trainer (A.N.M.)…”
Section: Interventionsmentioning
confidence: 99%
“…Despite the reported benefits of multimodal treatment for PFP, longer-term follow up data (5e20 years) indicates that more than 50% of individuals with PFP continue to experience symptoms and unfavourable outcomes (Lankhorst et al, 2016;Nimon, Murray, Sandow, & Goodfellow, 1998;Witvrouw, Danneels, Van Tiggelen, Willems, & Cambier, 2004). The development of a targeted intervention has been proposed to represent an approach that could positively impact long-term treatment outcomes (Crossley, Stefanik, et al, 2016;Glaviano & Saliba, 2016;Powers, Bolgla, Callaghan, Collins, & Sheehan, 2012;Witvrouw et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Rathleff, Roos, Olesen, & Rasmussen, 2015, demonstrated that an exercise therapy associated with patient' load management education had long term (24 months) positive effect on reducing pain and improve overall function in adolescents with PFP. However, an individual-based prescription should be aimed when treating or assessing patients with PFP regardless their age (Glaviano & Saliba, 2016). Regarding non-significant findings in ADL, it is important to elucidate that the ADL dimension contains items that do not represent challenging activities (e.g.…”
Section: Discussionmentioning
confidence: 99%